2013
DOI: 10.2147/amep.s44389
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating resident research into the dermatology residency program

Abstract: Programmatic changes for the dermatology residency program at The University of Texas Medical Branch were first introduced in 2005, with the faculty goal incorporating formal dermatology research projects into the 3-year postgraduate training period. This curriculum initially developed as a recommendation for voluntary scholarly project activity by residents, but it evolved into a program requirement for all residents in 2009. Departmental support for this activity includes assignment of a faculty mentor with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Greater research time during residency was associated with increased productivity during and after residency. The effectiveness of such structured systems for increasing resident scholarly activity has been demonstrated in various specialties, including surgery [15][16][17], internal medicine [18], orthopedic surgery [19], emergency medicine [20], family medicine [21,22], and dermatology [23]. A study from Japan demonstrated that residents' overall satisfaction with their Across specialties, the resident scholarly activity experience seems to be highly variable and suboptimal.…”
Section: Resident Scholarly Activity Leads To Future Academic Activitmentioning
confidence: 99%
“…Greater research time during residency was associated with increased productivity during and after residency. The effectiveness of such structured systems for increasing resident scholarly activity has been demonstrated in various specialties, including surgery [15][16][17], internal medicine [18], orthopedic surgery [19], emergency medicine [20], family medicine [21,22], and dermatology [23]. A study from Japan demonstrated that residents' overall satisfaction with their Across specialties, the resident scholarly activity experience seems to be highly variable and suboptimal.…”
Section: Resident Scholarly Activity Leads To Future Academic Activitmentioning
confidence: 99%
“…In contrast to the highly structured application process, Dermatology programs themselves vary widely in their features, approaches, demographics, and requirements for research. A minority of Dermatology residency programs have formally allotted time devoted to research within their curricula, and many programs' requirements for research are much broader and more open-ended [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, few programs have officially added a significant dedicated time to research to their residency curriculum. As a recent example, The University of Texas Medical Branch has successfully incorporated research into resident's daily activity [ 2 ]. The literature in assessing different attributes of the dermatology programs as well as its correlation with residency selection process is lacking.…”
Section: Introductionmentioning
confidence: 99%